L’éducation problématique du citoyen - Pierre Billouet (Recherches en Éducation)
Education of the citizen is problematic on several sides, and just one will be treated here, from Rousseau, who, in the Social Contract, provides the classic definition of autonomy: « obedience to a law which we prescribe to ourselves ». Autonomy implies the prescription of the law by citizens and the obedience by subjects. The article shows through several types of reading of Emile that the rousseauist education does not allow the formation of the citizen in the precise sense of co-legislator. But since autonomy is, on the other hand, the highest good according to the critical system of Kant, it is necessary to observe if this system gives some tools for education of the co-lawmaking. Finally the article clarifies several fundamental differences between both authors and invites to consider the current practices of the school education.